FUZZY TRANSLATIONS OF FUZZY H-IDEALS IN $BCK/BCI$-ALGEBRAS - Tapan Senapati (Journal of the Indonesian Mathematical Society, 2015)
In this paper, the concepts of fuzzy translation to fuzzy H-ideals in BCK/BCI-algebras are introduced. The notion of fuzzy extensions and fuzzy mul-tiplications of fuzzy H-ideals with several related properties are investigated. Also,the relationships between fuzzy translations, fuzzy extensions and fuzzy multiplica-tions of fuzzy H-ideals are investigated.DOI : http://dx.doi.org/10.22342/jims.21.1.200.45-58